ETHNOMATHEMATICS: EXPLORATION OF SEWU TEMPLE IN KLATEN - S. A., Dini Zulaekha; Sutama, Sutama (PATTIMURA UNIVERSITY, 2023)
The purpose of this study is to observe and describe a culture that surrounds the community as a whole related to Sewu Temple in a certain period based on fieldwork,then look for mathematical aspects of Sewu Temple in history, manufacturing processes, and mathematical concepts. The results of this study are presented in a qualitative form with an ethnographic approach that describes the history of Sewu Temple, the sources obtained are based on the results of interviews, observations and documentation, using an interview guide, the results of documentation and observations as a tool to obtain data sources. The temple building has several flat geometries including triangles, squares, trapezoids and rectangles, then there are spatial geometry in the form of cubes, blocks, tubes, and square pyramids which are concepts from the mathematics of geometric material. The results of this study are in the form of geometry material found in junior high schools related to mathematics learning activities. In this study, it is expected to be able to become material from learning and become a reference for future research studies related to culture and mathematics.